Investigation of the Benefits of Variable Orifice Dampers Used in an Earthquake Excited Three Story Structure - Gökdağ, Hakan; Turan, Gürsoy (Izmir Institute of Technology, 2009)
Research in the field of control of civil engineering structures is a continuing process. The three basic approaches to structural control may be defined as follows passive control systems,active control systems and semi-active control systems. These systems have received much attention recently because they have versatility and adaptability of active control systems. Although there is a wide variety of these energy absorbing devices, but all have one thing in common . they absorb energy from the structure.Semi-active control systems possess the advantages of both active and passive control systems. Variable orifice dampers are semi-active control devices that utilize the hydraulic fluid flow to generate controllable damping forces. Depending on the state of the structure, the energy absorbing property of the variable orifice dampers is changed on the fly. In this study, the proposed semi-active control algorithm and the effect of variable orifice damper for seismic response reduction is examined. To demonstrate the efficiency of the proposed semi-active control algorithm and the usefulness of variable orifice dampers,controlled and uncontrolled behaviour of the three story model structure subjected to earthquake forces are investigated numerically. The three story model structure in Civil Engineering Laboratory in .YTE is utilized for numerical simulations. The results indicate numerically that the proposed semi-active control algorithm with a variable orifice damper can be used effectively to reduce the earthquake induced structural vibrations.
Thesis (Master)--Izmir Institute of Technology, Civil Engineering, Izmir, 2009
Includes bibliographical references (leaves: 62-63)
Text in English; Abstract: Turkish and English
xi, 69 leaves
Keywords: TA658.44 .G61 2009; Earthquake resistant design